If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(n-4)-(3n-1)=-2=2n-1
We move all terms to the left:
-2(n-4)-(3n-1)-(-2)=0
We add all the numbers together, and all the variables
-2(n-4)-(3n-1)+2=0
We multiply parentheses
-2n-(3n-1)+8+2=0
We get rid of parentheses
-2n-3n+1+8+2=0
We add all the numbers together, and all the variables
-5n+11=0
We move all terms containing n to the left, all other terms to the right
-5n=-11
n=-11/-5
n=2+1/5
| -5(3x-5)=2(x-4)-35 | | 3f-(5(2f+11)-15=0 | | -2-6(5x-2)=190 | | 6(3x+2)=-48+6x | | 5x70=5 | | R^-10r+25=1 | | -0.5(x-22)=19+8x | | 13k+3k+k-11k-4K=10 | | -11t=132 | | R2-10r+25=1 | | -1/2(x-22)=19+8x | | 5b2=17 | | v−56=−78 | | 16k-16k+k=16 | | 7(4x-3)+2(6x+)=6(5x-4)-3(2x-6$+1 | | 27+2x=2(-x+6)-17 | | 12x-13=6x+9 | | 5x70=5x | | 7/8h+2=3/8h-2 | | 6s+3s-5s-s+2s=20 | | 14+19+q/3=17 | | 3(f-5)=5(2f+11 | | 188=m=80 | | 1900x+150=1500+275 | | 13k+k-13k=7 | | 4(-4x-21)=30(-9-2x) | | 2)a-1)-5a=7 | | -56=j+-22 | | 8x+4=9x=8 | | 32=f−54 | | 5^(-x+7)=12^7x | | 33+8b=5+4(2b+7) |